Aurora kinase A stabilizes FOXM1 to enhance paclitaxel resistance in triple‐negative breast cancer. Issue 9 (30th July 2019) - Yang, Na; Wang, Chang; Wang, Jian; Wang, Zifeng; Huang, Di; Yan, Min; Kamran, Muhammad; Liu, Quentin; Xu, BangLao
Abstract: Triple‐negative breast cancer (TNBC) has a relatively poor outcome. Acquired chemoresistance is a major clinical challenge for TNBC patients. Previously, we reported that kinase‐dead Aurora kinase A (Aurora‐A) could effectively transactivate the FOXM1 promoter. Here, we demonstrate an additional pathway through which Aurora‐A stabilizes FOXM1 by attenuating its ubiquitin in TNBC. Specifically, Aurora‐A stabilizes FOXM1 in late M phase and early G1 phase of the cell cycle, which promotes proliferation of TNBC cells. Knock‐down of Aurora‐A significantly suppresses cell proliferation in TNBC cell lines and can be rescued by FOXM1 overexpression. We observe that paclitaxel‐resistant TNBC cells exhibit high expression of Aurora‐A and FOXM1. Overexpression of Aurora‐A offers TNBC cells an additional growth advantage and protection against paclitaxel. Moreover, Aurora‐A and FOXM1 could be simultaneously targeted by thiostrepton. Combination of thiostrepton and paclitaxel treatment reverses paclitaxel resistance and significantly inhibits cell proliferation. In conclusion, our study reveals additional mechanism through which Aurora‐A regulates FOXM1 and provides a new therapeutic strategy to treat paclitaxel‐resistant triple‐negative breast cancer.